Pengaruh Media Sosial Dalam Meningkatkan Kesadaran Masyarakat Pesisir Terhadap Bencana Alam - Andriansah; Zaqi Muhammad Abdillah; Indra Setia Lesmana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study discusses the influence of social media in raising awareness among coastal communities regarding natural disasters. The rapid development of information and digital technology, which benefits all individuals, has now extended its benefits to various societal elements such as urban, mountainous, and coastal communities. The openness of information implemented by the government exemplifies the role of social media in enhancing the awareness of coastal communities towards natural disasters. Through qualitative analysis and interviews or discussions with members of coastal communities to obtain qualitative information about their experiences regarding disaster information received through social media, this research explores how social media can influence the understanding and responses of communities to disasters in coastal areas. The results of this study are expected to provide knowledge and insight into the role of social media in disaster risk mitigation and increasing awareness among coastal communities of impending natural disasters.